Flexible Bonding of the Phosph(V)azane Dianions [S(E)P(μ‐NtBu)]22−. Issue 8 (4th January 2018) - Plajer, Alex J.; Garcia‐Rodriguez, Raul; Rizzuto, Felix J.; Wright, Dominic S.
Abstract: Oxidation of the P III dianion [S−P(μ‐N t Bu)]2 2− (1 ) with elemental sulphur, selenium and tellurium gives the P V dianions [(S)(E)P(μ‐N t Bu)]2 2− (E = S (6 a ), Se (6 b ), Te (6 c )). Although6 c proves to be too unstable, the S, S‐dianion6 a and ambidentate S, Se‐dianion6 b are readily transferred intact to main group and transition metal elements, producing a range of new cage and coordination compounds. While their coordination characteristics are in many ways similar to closely‐related isoelectronic phosph(V)azane anions [(E)(RN=)P(μ‐N t Bu)]2 2−, the sterically unhindered nature of6 introduces an expanded range of coordination modes, that is, facial S, S‐ and Se, Se‐bonding as well as side‐on S, Se‐coordination. All of these bonding modes are observed for the amibidentate S, Se dianion6 b . Abstract : Three in one : the new P V dianions [(S)(E)P(μ‐N t Bu)]2 2− (E = S, Se, Te) are obtained by reactions of S, Se or Te with the P III dianion [(S)P(μ‐N t Bu)]2 2− . The S and Se dianions can readily be transferred intact to main group and transition metal centers, giving a range of new cages and coordination compounds in which the new dianions can exhibit facial S, S‐ or Se, Se‐bonding or side‐on S, Se bonding.